1998
DOI: 10.1200/jco.1998.16.10.3353
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dense therapy with weekly 1-hour paclitaxel infusions in the treatment of metastatic breast cancer.

Abstract: Weekly paclitaxel therapy is active and well tolerated in patients with metastatic breast cancer. Weekly therapy should be considered as a current clinical option for these patients and should be incorporated into future comparative clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
175
5
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(192 citation statements)
references
References 17 publications
11
175
5
1
Order By: Relevance
“…Seidman et al first explored the use of weekly schedules of paclitaxel alone [17] or combined with trastuzumab [10]. The results of these studies were encouraging in terms of activity and, particularly, regarding the toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seidman et al first explored the use of weekly schedules of paclitaxel alone [17] or combined with trastuzumab [10]. The results of these studies were encouraging in terms of activity and, particularly, regarding the toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggested an additive activity of trastuzumab when combined with paclitaxel [13,14] and several Phase I-II clinical studies have assessed the antitumoral activity and the tolerability of such a combination [12][13][14][15][16][17]. The combination of weekly paclitaxel with trastuzumab [10,15,16] produces extended cumulative exposure to the drug and ameliorates the toxicities associated with the standard tri-weekly administration [17], with mild, non-cumulative, hematologic toxicity allowing its administration for prolonged periods of time [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of them, paclitaxel and carboplatin [3,4], docetaxel and gemcitabine [5,6] and weekly paclitaxel [7][8][9] have demonstrated significant activity and manageable toxicity. Furthermore, the first of these combinations was found to be effective in a phase III trial [10], when compared to the combination of paclitaxel and epirubicin, in terms of overall response rate (ORR), survival and quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, paclitaxel was added to this regimen. Since weekly paclitaxel infusion has been reported to be more active than 3-weekly administration (Seidman et al, 1998), paclitaxel was administered on a sustained weekly schedule.…”
Section: Discussionmentioning
confidence: 99%